Erratum: Small Farm Resource Centers as Informal Extension Hubs in Underserved Areas: Case Studies from Southeast Asia - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Bicksler, A., Trail, P., Bates, R. M., Burnette, R. R., & Thansrithong, B. (2022). Small Farm Resource Centers as Informal Extension Hubs in Underserved Areas: Case Studies from Southeast Asia. Journal of International Agricultural and Extension Education, 29(2), 74-90" was incorrect as published. The correct DOI is: 10.4148/2831-5960.1060